PARTICIPATORY DESIGN: PENDEKATAN VISUAL-NARATIF UNTUK MEMBANGUN LITERASI FINANSIAL PADA REMAJA MARJINAL DI GAINESVILLE, FLORIDA: Participatory Design: A Visual-Narrative Approach to Building Financial Literacy among Marginalized Youth in Gainesville, Florida - Akbar Seknun (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Participatory Design: A Visual-Narrative Approach to Building Financial Literacy among Marginalized Youth in Gainesville, Florida. This research aims to explore how participatory design workshops can create a space for marginalized youth in Gainesville, Florida, specifically Project YouthBuild (PYB) students, to share their thoughts on financial literacy. Through two workshops, researchers and facilitators used a personal currency design approach based on the Miro platform. Participants not only designed their own money but also articulated their values, expectations, and understandings of money concepts, such as saving and investing. Results show that this creative, visual-based approach can bridge language and cultural gaps and foster active engagement. The novelty of this research lies in the application of a visual-narrative approach to financial literacy, which has rarely been explored in educational contexts for marginalized youth. This approach not only provides a more inclusive and contextual learning method but also introduces an alternative pedagogical model that places personal experience at the center of understanding financial concepts.